D-dimer: a biomarker for predicting disease severity and outcome in hospitalized children with COVID-19 and post COVID multisystem inflammatory syndrome - Saqlain, Nazish; Bari, Attia; C., Aimen; Sadiq, Masood (International Journal of Contemporary Pediatrics, 2023)
Background: COVID-19 has presented with varied signs and symptoms with raised inflammatory markers among which D-dimers have been highlighted right from the beginning. Objectives were to analyze the relationship of D-dimers with the disease severity and outcome of children with COVID-19 and MIS-C in a developing country. Methods: It was a retrospective study conducted at a pediatric tertiary care hospital from March 2020 to November 2021. Clinical and laboratory details of confirmed COVID-19 and post COVID-19 MIS-C cases were recorded. D-dimer testing was performed using Chemiluminescence technique. It’s relation with disease severity and predictive role for in-hospital mortality were established by using ROC curves and cut-off values were calculated by using SPSS-24. Results: Of 272 children, 182 were of COVID-19 and 90 were of MIS-C. The mean age for COVID-19 and MIS-C patients was 5.4±4.8 years and 6.4±3.5 years respectively. Mild disease was seen in 33% cases while 17.6% were critical and 56.2% had some under lying comorbidity at presentation. Mean D-dimers were significantly higher in children with severe disease, who required ICU admission and non-survivors as compared to those with mild or moderate disease, not requiring ICU care and survivors, both in COVID-19 and MIS-C patients. ROC curve identified D-dimer value of ≥4.58 µg/ml (AUC=0.845) for COVID-19 cases and ≥4.73 µg/ml (AUC=0.682) for MIS-C patients as predictive of mortality. Conclusions: Raised D-dimer level is a reliable predictor of disease severity and outcome in children with COVID-19 and MIS-C. The D-dimer value of 4.58 µg/ml for COVID-19 cases and 4.73µg/ml for MIS-C patients was found to be the cut-off levels for predicting mortality